2017
DOI: 10.1084/jem.20160875
|View full text |Cite
|
Sign up to set email alerts
|

Human venous valve disease caused by mutations in FOXC2 and GJC2

Abstract: Patients with mutations in FOXC2 and GJC2 have reduced venous valve number and leaflet length. Experiments in mice by Lyons et al. show that Foxc2-Calcineurin-Nfatc1, and Gja4, Gjc2, Gja1 regulate valve-forming cell organization. Foxc2, Calcineurin-Nfatc1, and blood flow regulate leaflet growth/maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 55 publications
(135 reference statements)
4
68
0
Order By: Relevance
“…The Ca 2+ /NFAT signaling pathway is a crucial signaling pathway for maintaining the normal physiological functions of the cardiovascular system as well as pathophysiology. Studies have reported that the Ca 2+ /NFAT signaling pathway is essential for coronary angiogenesis and venous valves development during vascular plexus formation [37][38][39] . Reports have shown that the NFAT pathway may be the main signaling Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Ca 2+ /NFAT signaling pathway is a crucial signaling pathway for maintaining the normal physiological functions of the cardiovascular system as well as pathophysiology. Studies have reported that the Ca 2+ /NFAT signaling pathway is essential for coronary angiogenesis and venous valves development during vascular plexus formation [37][38][39] . Reports have shown that the NFAT pathway may be the main signaling Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The observed discrepancy between intracellular and surface P-selectin expression is consis-through upregulation of the FOXC2, GATA2, and PROX1 transcription factors in perivalvular endothelial cells (11)(12)(13)(14)(15)(16)(17), and sustained expression of FOXC2 and GATA2 is required to maintain lymphatic valves in the mature animal (16,18). Since venous valves are morphologically identical to lymphatic valves and also require FOXC2 and PROX1 to develop (19)(20)(21)(22), we assessed whether this transcriptional program might be maintained in the endothelium surrounding the mature venous valve. Immunostaining of mouse saphenous veins from wild-type animals and PROX1-GFP transgenic reporter animals revealed that FOXC2 and PROX1 were specifically expressed in endothelial cells lining both sides of the venous valve and the adjacent valve sinus, but were undetectable in nonvalvular, lumenal venous endothelium ( Figure 1, A and B).…”
Section: Perivalvular Venous Endothelial Cells Express Foxc2 and Prox1mentioning
confidence: 99%
“…It has recently been reported that human venous valve disease may be caused by mutations in the GJC2 gene. Patients with such mutation show reduced number and length of venous valves (20). Interestingly, Cx47 −/− mice display disrupted organization and reduced proliferation of venous valve-forming ECs, which may underlie the venous valve defects seen in patients with GJC2 mutations (20).…”
Section: Connexins In Lymphatic Edemamentioning
confidence: 99%
“…Patients with such mutation show reduced number and length of venous valves (20). Interestingly, Cx47 −/− mice display disrupted organization and reduced proliferation of venous valve-forming ECs, which may underlie the venous valve defects seen in patients with GJC2 mutations (20). Comparable changes in venous valve-forming ECs were observed in Cx37 −/− and Cx43 −/− mouse embryos, suggesting that it might be relevant to search for mutations in GJA4 and GJA1 genes in venous valve disease patients.…”
Section: Connexins In Lymphatic Edemamentioning
confidence: 99%